Indirect costs of depression and other mental and behavioural disorders for Australia from 2015 to 2030 - Schofield, Deborah (BJPsych Open, 2019)
BACKGROUND: The impact of mental disorders has been assessed in relation to longevity and quality of life; however, mental disorders also have an impact on productive life-years (PLYs). AIMS: To quantify the long-term costs of Australians aged 45–64 having lost PLYs because of mental disorders. METHOD: The Survey of Disability, Ageing and Carers 2003, 2009 formed the base population of Health&WealthMOD2030 – a microsimulation model integrating output from the Static Incomes Model, the Australian Population and Policy Simulation Model, the Treasury and the Australian Burden of Disease Study. RESULTS: For depression, individuals incurred a loss of AU$1062 million in income in 2015, projected to increase to AU$1539 million in 2030 (45% increase). The government is projected to incur costs comprising a 22% increase in social security payments and a 45% increase in lost taxes as a result of depression through its impact on PLYs. CONCLUSIONS: Effectiveness of mental health programmes should be judged not only in terms of healthcare use but also quality of life and economic well-being. DECLARATION OF INTEREST: None.